Analisis Bibliometrik pada Database Dimensions dalam Penelitian Radikalisme Islam di Indonesia - Diana Artika; Busro Busro (Gunung Djati Conference Series, 2023)
Radicalism is a response to the conditions that are happening, the response is then manifested in the form of evaluation, rejection, and even violent resistance. The phenomenon that is common in Indonesia in terms of radicalism is related to religion. This research uses qualitative methods to identify research trends in the theme of Islamic Radicalism. As well as using bibliometric analysis by using the Dimensions database. There are five stages carried out in this study, namely keyword determination, data search, article selection, data validation, and data analysis. In writing a data analysis report on the key word taken, namely "Islamic Radicalism in Indonesia". Namely by collecting data on research categories, trends or developments per year, researchers or authors, affiliations, and the location of article publications or journal names. That the results of this study show that the issue of Islamic radicalism in Indonesia has the attraction of researchers rapidly until now.